Comparative Effectiveness of Simulation versus Serious Game for Training Nursing Students in Cardiopulmonary Resuscitation: A Randomized Control Trial. (24th March 2021) - Farsi, Zahra; Yazdani, Mahdieh; Butler, Samantha; Nezamzadeh, Maryam; Mirlashari, Jila
Abstract : Background . The proper implementation of cardiopulmonary resuscitation (CPR) is crucial in saving patients. Purpose . This study was aimed at evaluating the difference in educating nursing students on CPR when using the traditional simulation training with a mannequin versus a more novel serious game training on the smartphone platform. Methods . This randomized control trial was conducted in 2018-2019. Through purposive sampling, 56 nursing students were selected and randomly assigned to three groups: a simulation-based CPR training, CPR training using a serious game on the smartphone platform, and a control group that received no CPR training. Each student was evaluated pre- and posttraining on CPR knowledge and skill. Results . Both the simulation and serious game training groups increased CPR abilities two weeks after training. The control group did not show improvement in skill or knowledge of CPR. The simulation and serious game intervention groups demonstrated better scores on the knowledge questionnaire and on the CPR skill demonstration in comparison to the control group. However, the simulation group and the serious game group showed no significant difference in knowledge (9.55 ± 2.81 vs. 7.77 ± 2.46 ; p = 0.065 ) or CPR skill demonstration (27.17 ± 2.81 vs. 25.72 ± 3.98 ; p = 0.988 ). The overall scores for CPR knowledge did not meet minimum expectations (70% score) in either the simulation (47.75%) or serious game (38.85%) group. However, both groups demonstrated adequate CPR skill on demonstration (simulation 87.64% and serious game 83.06%). Conclusions . Both the simulation and serious game training groups were found to increase CPR skill. CPR training would likely benefit from a multimodal approach to education.